Heartland [compact disc, unabridged] : a memoir of working hard and being broke in the richest country on Earth - Smarsh, Sarah (Audioworks, imprint of Simon & Schuster Audio, 2018)
During Smarsh's turbulent childhood in Kansas in the '80s and '90s, the forces of cyclical poverty and the country's changing economic policies solidified her family's place among the working poor. Her personal history affirms the corrosive impact intergenerational poverty can have on individuals, families, and communities. Combining memoir with powerful analysis and cultural commentary, this is an uncompromising look at class, identity, and the particular perils of having less in a country known for its excess.